Sorafenib as first- or second-line therapy in patients with metastatic renal cell carcinoma in a community setting. (October 2014) - Procopio, Giuseppe; Derosa, Lisa; Gernone, Angela; Morelli, Franco; Sava, Teodoro; Zustovich, Fable; De Giorgi, Ugo; Ferrari, Vittorio; Sabbatini, Roberto; Gasparro, Donatello; Felici, Alessandra; Burattini, Luciano; et al.
ABSTRACT Aim: The Italian Retrospective Analysis of Sorafenib as First or Second Target Therapy study assessed the efficacy and safety of sorafenib in metastatic renal cell carcinoma patients treated in the community.Patients & methods: Patients receiving first- or second-line single-agent sorafenib between January 2008 and December 2010 were eligible. Retrospective data collection started in 2012 and covers at least 1-year follow-up. The primary end point was overall survival (OS).Results: Median OS was 17.2 months (95% CI: 15.5–19.6): 19.9 months (95% CI: 15.9–25.3) in patients treated with first-line sorafenib and 16.3 months (95% CI: 13.1–18.2) with second-line sorafenib. Overall median (95% CI) progression-free survival was 5.9 months (95% CI: 4.9–6.7): 6.6 (95% CI: 4.9–9.3) and 5.3 months (95% CI: 4.3–6.0) in first- and second-line patients, respectively.Conclusion: The efficacy and safety of sorafenib in routine community practice was generally good, especially in relation to OS in patients treated in the second line, where results were similar to those seen in recent prospective clinical trials.